A STUDY OF VOCAL PERFORMANCE ACHIEVEMENT THROUGH A CHOIR INSTRUCTION PACKAGE BASED ON THE CONCEPTS OF ZOLTAN KODALY AND CARL ORFF AMONG GRADE 8 STUDENTS AT CHUMCHON WATBANGKHAN SCHOOL - Khodanu, Thanaphong; Wangphanich, Chanick (Fine Arts Journal: Srinakharinwirot University, 2026)
Background and Objectives: The researchers created a choir instruction package based on the concepts of Zoltan Kodaly and Carl Orff, to develop students’ understanding of harmonic singing skills and improve their music learning achievement. The objectives of this research were to examine the learning achievement in the Basic Arts subject, specifically Western song singing, using a choir instruction package in a harmonic format based on the concepts of Zoltan Kodaly and Carl Orff, among grade 8 students at Chumchon Watbangkhan School, and to investigate students’ satisfaction on the use of the choir instruction package in a harmonic format based on the concepts of Zoltan Kodaly and Carl Orff. Methods of Study: This study employed an experimental research design using a one-group pretest-posttest approach. The sample group consisted of 26 Grade 8 students from Class 2 enrolled in the Basic Arts subject during the second semester of the 2025 academic year at Chumchon Wat Bang Khan School. Cluster sampling was employed to select a group in which most students experienced difficulties in singing skills. The research instruments consisted of: 1) the experimental tool, namely the choir instruction package in a harmonic format based on the concepts of Zoltan Kodaly and Carl Orff; and 2) data collection instruments, including a vocal achievement test (Pretest and Posttest), and a student satisfaction survey on the use of the choir instruction package. Data analysis included a comparison of learning achievement before and after the use of the choir instruction package based on the concepts of Zoltan Kodaly and Carl Orff using a dependent samples t-test, as well as an analysis of student satisfaction among grade 8 students using mean and standard deviation. Key Findings: After learning through the choir instruction package based on the concepts of Zoltan Kodaly and Carl Orff, students’ vocal achievement scores were significantly higher than their pre-instruction scores at the .05 level of statistical significance. Furthermore, students’ satisfaction with the choir instruction package for Western song singing was evaluated at the highest level (x̄ = 25.31, SD = 1.47). Significance of the study: The findings of this study provide teachers with an instructional approach that can be applied to activities for developing students’ vocal learning and further adapted for teaching practices in the future. Conclusion and future directions: The choir instruction package based on the concepts of Zoltan Kodaly and Carl Orff met the study objectives. It was suitable for students in terms of content and duration, attraction, and engagement. The package was engaging and promoted innovative learning experiences while encouraging self-directed learning. Furthermore, it enabled students to apply acquired knowledge to further musical practice, and achieve higher earning results. In summary, students are satisfied with the choir instruction in a harmonic format, using the concepts of Zoltan Kodaly and Carl Orff. The instruction provided students with options for reviewing knowledge and repeating practice easily, which meets the needs of contemporary learning environments.